ADSORPTION STUDY OF LEAD (Pb²⁺) IONS USING CASSAVA PEEL BIOCHAR: EFFECT OF pH AND CONTACT TIME - Elfia, Mega; Etriyanto Arman; Eduwin Saputra; Alfin Surya; Yoravika Dwiwibangga; Vicka Andini; Aidil Onasis; Nadya Br Debora (JURNAL KATALISATOR, 2025)
This study evaluates the adsorption performance of NaOH-activated cassava peel biochar (Manihot esculenta Crantz) for the removal of Pb²⁺ ions from aqueous solutions, with particular focus on the effects of solution pH and contact time. Cassava peel biochar was produced via pyrolysis at 180–350 °C and chemically activated using 0.1 M NaOH. Surface functional groups and morphology were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy–Energy Dispersive X-ray (SEM–EDX). Batch adsorption experiments were conducted by varying solution pH (3–8) and contact time (30–120 min), while Pb²⁺ concentrations before and after adsorption were analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that solution pH significantly affected Pb²⁺ adsorption, with the highest adsorption capacity of 9.94 mg/g achieved at pH 5. Contact time also influenced adsorption performance, and the optimum condition was obtained at 90 min, yielding a maximum adsorption capacity of 9.94 mg/g. These findings indicate that NaOH-activated cassava peel biochar exhibits stable and effective Pb²⁺ adsorption under slightly acidic conditions and moderate contact time, highlighting its potential as a low-cost and environmentally friendly adsorbent for Pb²⁺ removal from contaminated wastewater.